Reduced risk of NSAID‐Induced adverse events with concomitant use of misoprostol (MICRO study). Issue 7 (16th June 2022) - Munger, Mark A.; Nelson, Scott D.; Teng, Chia‐Chen; Cheung, Alfred K.; Sauer, Brian C.
Abstract: Background: Non‐steroidal anti‐inflammatory drugs (NSAIDs) are one of the most frequently used medications for pain, even though they increase the risk for adverse cardiovascular events. Objectives: The objective of this study was to determine cardiovascular, cerebrovascular, and renal event rates between NSAIDs versus NSAIDs plus misoprostol. Methods: A population‐based historical cohort of U.S. veterans receiving prescription NSAIDs (1, 681, 609) versus NSAIDs plus misoprostol (5972 misoprostol users) was followed for 5 years. In an intent‐to‐treat analysis, NSAID and NSAID plus misoprostol groups were compared using propensity score‐weighted Poisson regression models to estimate incident rate ratio (IRR) and Cox regression to estimate hazard ratio (HR). Results: The most prescribed NSAIDs were diclofenac and ibuprofen. The mean follow‐up was 35.2 ± 14.5 months. There were 439 total cardio‐renal events (5.62/1000 patient‐months) in the NSAID group and 419 patients (5.01/1000 patient‐months) in the NSAID plus misoprostol group (Hazard Ratio (HR): 0.89; 95% confidence interval [CI]: 0.78–1.019; p = 0.09). The risk of cardiovascular event was lower in the NSAID plus misoprostol group (HR: 0.56; 95% CI: 0.34–0.93; p < 0.0001). Cerebrovascular event rates were lower in the NSAID plus misoprostol group (HR: 0.74; 95% CI: 0.60–0.94, p < 0.0001) and for renal (HR: 0.67; 95% CI: 0.49–0.89, p < 0.0001) events. All‐cause mortality rate was not different between the two groups (HR: 1.05; 95% CI: 0.88–1.25, p = 0.61). Conclusion: Compared with NSAID use alone, the concomitant use of NSAID plus misoprostol is associated with a reduced risk of NSAID‐induced cardiovascular, cerebrovascular, and renal adverse events. These data support the development of a safer NSAID when combined with misoprostol.